PELESTARIAN MUSIK TRADISIONAL GANDANG SARUNAI MASYARAKAT ALAM SURAMBI SUNGAI PAGU DI NAGARI SAKO UTARA PASIA TALANG - Zulhendri Zulhendri; Wimbrayardi Wimbrayardi; Esy Maestro (FBS Universitas Negeri Padang, 2014)
Abstract This study was aimed at describing the preservation of traditional music of Gandang Sarunai in Nagari Sako Pasia Talang Alam Sarambi Sungai Pagu. This was a quatitative research which used descriptive analysis approach. The instruments of the research were camera, note-book and list of interview. The data was collected through observation, interview and photography. It then was classified into primary and secondary data. The result of the study indicated thet the preservation of traditional music of Gandang Sarunai in Nagari sako Utara Pasia Talang was done in non-formal way; learning throughy observing or watching the show, and legating the skill hereditarily or through art groups. There were three phases done in acquiring the skills of playing Gandang Sarunai through and so were in art groups. In society, Gandang Sarunai was performed in the ceremony of Pengangkatan Penghulu, wedding party, building Rumah Gadang, and welcoming the noble guests. Gandang Sarunai also had four function which were as emotional expression, entertainment, esthetics, and communication. Keywords : Art, gandang sarunai, penggunaan, pelestarian, fungsi